Medical telementoring using an augmented reality transparent display - Andersen, Daniel; Popescu, Voicu; Cabrera, Maria Eugenia; Shanghavi, Aditya; Gomez, Gerardo; Marley, Sherri; Mullis, Brian; Wachs, Juan P. (Surgery, 2016)
The goal of this study was to design and implement a novel surgical telementoring system called the System for Telementoring with Augmented Reality (STAR) that uses a virtual transparent display to convey precise locations in the operating field to a trainee surgeon. This system was compared with a conventional system based on a telestrator for surgical instruction. A telementoring system was developed and evaluated in a study which used a 1 × 2 between-subjects design with telementoring system, that is, STAR or conventional, as the independent variable. The participants in the study were 20 premedical or medical students who had no prior experience with telementoring. Each participant completed a task of port placement and a task of abdominal incision under telementoring using either the STAR or the conventional system. The metrics used to test performance when using the system were placement error, number of focus shifts, and time to task completion. When compared with the conventional system, participants using STAR completed the 2 tasks with less placement error (45% and 68%) and with fewer focus shifts (86% and 44%), but more slowly (19% for each task). Using STAR resulted in decreased annotation placement error, fewer focus shifts, but greater times to task completion. STAR placed virtual annotations directly onto the trainee surgeon's field of view of the operating field by conveying location with great accuracy; this technology helped to avoid shifts in focus, decreased depth perception, and enabled fine-tuning execution of the task to match telementored instruction, but led to greater times to task completion.